2019
DOI: 10.1055/s-0039-1698481
|View full text |Cite
|
Sign up to set email alerts
|

Extra-axial Cerebellopontine Angle Adult Medulloblastoma: An Unusual Presentation at an Unusual Site

Abstract: Medulloblastoma is a rare adult primary brain tumor and its presence in the cerebellopontine angle (CPA) constitutes an even rarer site for origin. There are only 40 reported cases of CPA medulloblastoma in the literature, with most being intra-axial and occurring in the pediatric population. Extra-axial CPA medulloblastoma in adults are extremely rare and only 10 adult cases have been reported in world literature.We report a rare case of primary extra-axial CPA medulloblastoma occurring in an adult. We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…There have been only 12 reported cases of extra-axial MB in the adult literature [ Table 1 ]. [ 2 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been only 12 reported cases of extra-axial MB in the adult literature [ Table 1 ]. [ 2 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…There have been only 12 reported cases of extra-axial MB in the adult literature [Table 1]. [2,[4][5][6][7][8][9][10][11][12][13] A review of all reported cases shows that CPA MB is twice more common in males in their 2 nd -3 rd decade, with the classic variety seen in more than half of the cases. Ten out of 12 reports so far published considered meningioma as a provisional diagnosis based on broad tentorial attachment, despite heterogeneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations